Makna Pengalaman Mahasiswa terhadap Penipuan Jual-Beli Akun Game Online dan Implikasinya terhadap Pengelolaan Keuangan Pribadi - Khaerullah; Wa Ode Rayyani (Jurnal Ekonomi dan Bisnis Digital, 2025)
This research aims to explore in depth the personal experiences of university students who have become victims of online game account trading fraud and how such experiences influence their financial behavior and management. Utilizing a narrative qualitative approach, the study seeks to uncover the subjective meanings behind these digital fraud events through individual storytelling and reflection. The findings reveal that although the fraud initially resulted in emotional and financial distress, it ultimately triggered critical awareness, leading to more cautious, organized, and responsible financial behaviors among the students.